Long-term use of a 4% sodium cromoglicate cutaneous emulsion in the treatment of moderate to severe atopic dermatitis in children. (2nd November 2015) - Edwards, Alan Martin; Bibawy, Dalia; Matthews, Sharon; Tongue, Nicky; Arshad, Syed Hasan; Lødrup Carlsen, Karin; Øymar, Knut; Pollock, Ian; Clifford, Rollo; Thomas, Anne; Gamanya, Rufaro; Vyas, Jui; et al.
Abstract: Introduction : Sodium cromoglicate (SCG), a chromone with anti-inflammatory, anti-itch and anti-allergic properties. We report a long-term study of a 4% aqueous solution of SCG in children with moderate to severe atopic dermatitis (AD). Materials and methods : Children aged 1 to 12 years with AD were entered into a 12-week randomised clinical trial (RCT), followed by 12 months open treatment with known 4% SCG emulsion (Altocrom®). Primary endpoint was change in SCORAD score. Secondary endpoints included symptom severity, Quality of Life, concomitant treatment usage, global assessments. Results : One hundred and seventy-seven subjects entered, 118 treated with 4% SCG emulsion and 59 with vehicle: 128 completed 12 months in open study. SCORAD score reduced during RCT by −15.3 (−33%) on 4% SCG emulsion and −18.0 (−39%) on vehicle: p  = 0.2331. After 12 months reduction was 56%. No secondary endpoint showed differences between treatments during RCT. Thirty-two subjects reported treatment related events during RCT and open trial. Eleven (7%) reported application site discomfort. Most were reported as mild and most resolved without intervention and the study drug was stopped in one case only. Conclusions : SCG 4% cutaneous emulsion was well tolerated in children treated for 15 months.